Analisis Faktor-Faktor yang Mempengaruhi Continued Intention to Use Twitch Menggunakan Tam yang Dimodifikasi - Fajar Kurnia; Arista Pratama (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Twitch is a global live-streaming platform that has experienced rapid international growth; however, its usage level in Indonesia remains relatively low, creating a research gap regarding the factors that influence user acceptance. This study focuses on Twitch users in Indonesia by analyzing the factors that affect acceptance and continued usage intention using a modified Technology Acceptance Model (TAM), enriched with constructs from Perceived Value Theory and service-specific variables related to live streaming. The research employs a quantitative method with 140 Indonesian Twitch users selected through purposive sampling and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The examined variables include Convenience Value, Monetary Value, Social Value, Emotional Value, Effort Expectancy, Performance Expectancy, Perceived Value, Perceived Enjoyment, Addiction, and Perceived Risk. The findings indicate that Convenience Value, Social Value, and Emotional Value significantly influence Perceived Value, while Performance Expectancy has a significant effect on Personal Innovativeness. Moreover, Perceived Value, Perceived Enjoyment, and Addiction are found to significantly influence Continued Intention to Use. These results highlight that convenience, social value, emotional value, functional benefits, enjoyment, and content addiction are key factors in shaping user acceptance and sustained usage intention of Twitch in Indonesia.